2017
DOI: 10.1055/s-0043-107244
|View full text |Cite
|
Sign up to set email alerts
|

T372R Mutation Status in Yin Yang 1 Gene in Insulinoma Patients

Abstract: Insulinomas are rare pancreatic neuroendocrine tumors. The genetic causes underlying insulinoma are still being investigated. Recently, 3 independent studies reported a recurrent somatic mutation in YY1 gene (C>G; Thr372Arg) among insulinoma patients belonging to Chinese and Western Caucasian populations, which was found to increase insulin secretion by β-cells. However, the status of this key gene variation remains unknown in patients of other ethnicities. We, therefore, screened Indian sporadic insulinoma pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
0
4
0
3
Order By: Relevance
“…Mutation prevalence ranged from 10% to 30% of cases, with the higher proportion found in Asian patients (191–194). A Sanger sequencing study from India did not find this hotspot Yin Yang 1 mutation in 17 insulinomas (195), whereas a similar study on 23 US patients found two hotspot mutations in 23 (8%) insulinomas (196). This mutation was associated with a late onset of the tumor and was reported to affect YY protein transcriptional activity.…”
Section: An Updated Landscape Of the Molecular Alterations Of Gep-netsmentioning
confidence: 87%
“…Mutation prevalence ranged from 10% to 30% of cases, with the higher proportion found in Asian patients (191–194). A Sanger sequencing study from India did not find this hotspot Yin Yang 1 mutation in 17 insulinomas (195), whereas a similar study on 23 US patients found two hotspot mutations in 23 (8%) insulinomas (196). This mutation was associated with a late onset of the tumor and was reported to affect YY protein transcriptional activity.…”
Section: An Updated Landscape Of the Molecular Alterations Of Gep-netsmentioning
confidence: 87%
“…However, four different WES studies of sporadic insulinomas found <2% with somatic MEN1 mutation, but rather they found a somatic heterozygous recurrent mutation in the Yin Yang 1 ( YY1 ) gene (c.C1115G/p.T372R) in 30%, 33% and 13% of tumor samples (Cao, et al 2013; Cromer, et al 2015; Lichtenauer, et al 2015; Wang, et al 2017). Another study from India did not find this YY1 mutation in their insulinoma samples (Irshad, et al 2017). To determine the frequency and consequence of the recurrent YY1 mutation we analyzed a cohort of 23 sporadic insulinomas.…”
Section: Dear Editormentioning
confidence: 94%
“…Lichtenauer et al analyzed 47 samples from German insulinoma patients and found that the frequency of the YY1 T372R mutation was 13% (6/47), significantly lower than that in the Chinese and Caucasian patient cohorts [ 66 ]. In addition, Irshad et al screened patients with sporadic insulinoma in India for the YY1 T372R mutation and found none of the above mentioned missense mutations at YY1 codon 372 in any of the 17 (100%) islet tissues analyzed [ 70 ]. Therefore, differences in genetic makeup based on ethnicity may affect disease susceptibility.…”
Section: Relationship Between Yy1 and The Onset Of Insulinomamentioning
confidence: 99%